Factors affecting the interests in entrepreneurs towards E-commerce / Nurul Afiqah Sakir - Sakir, Nurul Afiqah (Faculty of Business and Management, 2018)
This research is conducted to determine the factors affecting the interests in entrepreneurs towards e-commerce in Kuala Lumpur area and to find out the most influenced factors on this matter of interest towards e-commerce. The study was conducted by distributing 273 sets of questionnaires conveniently in a seminar at Seminar Room 1, Ministry of International Trade and Industry, Kuala Lumpur on 20th December 2017 at 8 am until 5 pm. Based on data findings, it shows that all of the independent variables; need of competence, relatedness and autonomy have positive relationship towards interest towards e-commerce. Besides that, the hypotheses that were developed at the beginning stage of research process; (H1) the needs for competence has relationship with entrepreneurs’ interest towards e-commerce, (H2) the relatedness factor has relationship with entrepreneurs’ interest towards e-commerce and (H3) the autonomy factor has relationship with entrepreneurs’ interest towards e-commerce are supported as the results. The most influential factor of all the variables is relatedness factor which describes the belongingness of the individual or entrepreneur in his daily life between his or her parents, teacher, supervisors or colleagues.